002 Sudden cardiac death risk stratification in patients with mild dilated cardiomyopathy. (3rd April 2017) - Halliday, Brian P; Gulati, Ankur; Ali, Aamir; Guha, Kaushik; Newsome, Simon; Arzanausikaite, Monika; Vassiliou, Vassilios S; Lota, Amrit; Tayal, Upasana; Khalique, Zohya; Izgi, Cemil; Alpendurada, Francisco; et al.
Abstract : Background: The DANISH trial emphasised that the selection of patients with dilated cardiomyopathy (DCM) for implantable cardioverter defibrillators (ICD) needs to be improved. Registries demonstrate that the major burden of sudden cardiac death (SCD) occurs in those with a left ventricular ejection fraction (LVEF) >35%. Those at high-risk of SCD with milder reductions in LVEF may gain greater quality-adjusted life years from successful ICD therapy compared to those with more severe reductions, due to a lower risk of death from competing non-sudden causes. Variables that identify patients with milder reductions in LVEF at high-risk of SCD are required. Methods: We prospectively investigated the utility of mid-wall late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) to predict SCD and aborted SCD in consecutive patients with DCM and LVEF >40% seen in our cardiomyopathy service or referred for CMR between 2000 and 2011. Those with potential pre-existing indications for ICD implantation were excluded. The presence of LGE was determined by a specialist blinded to clinical data. A panel blinded to CMR data adjudicated end-point occurrences. Results: Of 399 patients (145 women, median age 50 years, median LVEF 50%) followed for a median of 4.6 years, 18 of 101 (17.8%) with LGE reached the pre-specified end-point, compared to 7 of 298 (2.3%) without (HR 9.2; 95% CI 3.9–21.8; p<0.0001) ( Figure 1) . Nine patients (8.9%) with LGE compared to 6 (2.0%) without (HR 4.9; 95% CI 1.8–13.5; p=0.002) died suddenly, whilst 10 patients (9.9%) with LGE compared to 1 (0.3%) without (HR 34.8; 95% CI 4.6–266.6; p<0.001) had aborted SCD. Following adjustment based on propensity score, LGE predicted the composite end-point (HR 8.0; 95% CI 3.3–19.5; p<0.0001), SCD (HR 4.6; 95% CI 1.6–13.1; p=0.005) and aborted SCD (HR 32.9; 95% CI 4.3–249.9; p<0.001). Estimated hazard ratios for the primary end-point for patients with a LGE extent of 0%–2.5%, 2.5%–5% and >5% compared to those without LGE were 10.6 (95%CI 3.9–29.4), 4.9 (95% CI 1.3–18.9) and 11.8 (95% CI 4.3–32.3). Conclusion: Mid-wall LGE identifies patients with DCM and a LVEF >40% with an 8-fold increased risk of SCD and aborted SCD, who may benefit from ICD implantation. Acknowledgements: BPH is supported by a British Heart Foundation Clinical Research Training Fellowship. The study has also been supported by the Alexander Jansons Foundation and CORDA.